Determinants of Malaysian farmers' choice of adaptation strategies for adapting to climate change in Kedah Malaysia - Afroz, Rafia; Akhtar, Rulia (Knowledgia Scientific, 2017)
In Malaysia, the climate is changing. So, the associated risks are expected to have serious impacts on agriculture and national food sufficiency level which in turn will affect the rural farmers for whom agriculture is the main source of income. The level of impacts will mainly depend on the awareness and the level of adaptation in response to the changing climate. It was thus important to analyze which factors may affect the decision of the farmers whether they adapt with the climate change in order to implement appropriate policy measures for the sake of the affected farmers. The objective of the study was to examine the perception of the farmers towards climate change and the factors that influence farmersʼ choice of adaptation measures to climate change.